A sequential approach to integrated energy modeling in South Africa - Arndt, Channing; Davies, Rob; Gabriel, Sherwin; Makrelov, Konstatin; Merven, Bruno; Hartley, Faaiqa; Thurlow, James (Elsevier, 2016)
We develop a sequential approach to link a bottom-up energy sector model to a detailed dynamic general equilibrium model of South Africa. The approach is designed to simultaneously address the shortcomings and maintain the attractive features of detailed energy sector and general equilibrium models. It also reflects common country-level energy planning processes. We illustrate the capabilities of this integrated bottom-up approach by analyzing the implications of (i) a carbon tax, (ii) liberalization of import supply restrictions in order to exploit regional hydropower potential, and (iii) a combined policy where both carbon taxes and import liberalization are pursued. For the combined scenario, our results suggest substantial emissions reductions relative to Baseline at essentially no cost to economic growth but about a one percent reduction in employment. We conclude that a regional energy strategy, anchored in hydropower, represents a potentially inexpensive approach to decarbonizing the South African economy. The strategy also has political economy attractions in that the combined approach reduces the burden of adjustment of politically sensitive sectors.